2011
DOI: 10.1007/s00063-011-0048-z
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaktische intraaortale Ballongegenpulsation bei herzchirurgischen Hochrisikopatienten

Abstract: Prophylactic preoperative IABP insertion in EuroSCORE-stratified high-risk patients is not associated with decreased 30-day mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…The authors reported that early decision for IABP insertion and performing percutaneous IABP insertion in the preoperative ICU setting reduced mortality. In parallel with this finding, Christenson et al [16] and Metz et al [17] also found more promising results in terms of mortality, duration of mechanical ventilation, and length of stay in the ICU in patients with IABP inserted preoperatively in the ICU. In our study, the mean length of stay in the ICU in the patients with IABP inserted was found to be 7.5 days in Group 1 and 7 days in Group 2, indicating no statistically significant difference.…”
Section: Discussionmentioning
confidence: 69%
“…The authors reported that early decision for IABP insertion and performing percutaneous IABP insertion in the preoperative ICU setting reduced mortality. In parallel with this finding, Christenson et al [16] and Metz et al [17] also found more promising results in terms of mortality, duration of mechanical ventilation, and length of stay in the ICU in patients with IABP inserted preoperatively in the ICU. In our study, the mean length of stay in the ICU in the patients with IABP inserted was found to be 7.5 days in Group 1 and 7 days in Group 2, indicating no statistically significant difference.…”
Section: Discussionmentioning
confidence: 69%
“…The benefit of the Impella 5.5 during cardiac surgery is to provide forward flow while adequately unloading the left ventricle; this prevents post-cardiotomy shock and minimizes the need for high dose inotropic and pressor support [ 3 ]. Avoiding high dose inotropic and pressors support in reduced LV function mitigates the risk of LV failure and end-organ damage postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…A potential solution is the use of mechanical circulatory support (MCS) in the perioperative period. An intra-aortic balloon pump (IABP) has been used as MCS in patients going for high-risk cardiac surgery with the intent to reduce surgical risk, however; studies have demonstrated contradictory results of IABP in high-risk patients [ 3 ]. Extracorporeal membrane oxygenation (ECMO) may be used; however, it is limited due to the requirement for anticoagulation, patient immobilization, and bleeding risk.…”
Section: Introductionmentioning
confidence: 99%
“…Le timing de l'insertion du BCPIA en périopératoire chez les patients à haut risque reste un sujet très controversé [ 8 , 9 , 12 , 17 19 ]. Dans notre étude seulement 2 patients avaient un BCPIA en préopératoire sans que la différence ne soit significative.…”
Section: Discussionunclassified